MENINGKATKAN AKTIVITAS BELAJAR, KETERAMPILAN KERJASAMA, BERPIKIR KRITIS, DAN HASIL BELAJAR MENGGUNAKAN MODEL CANGKAL DAN MEDIA WORDWALL MUATAN BAHASA INDONESIA PADA SISWA KELAS V SDN SUNGAI MIAI 8 BANJARMASIN - Fahrizal, Muhammad Rizki; Dwitalia Sari, Dessy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by the low levels of student activity, collaboration skills, critical thinking, and learning outcomes in Grade V of SDN Sungai Miai 8 Banjarmasin. These issues were caused by one-way teaching, minimal interaction, lack of varied instructional models and media, and a monotonous classroom atmosphere. The purpose of this research was to describe teacher activity and analyze improvements in student engagement, collaboration skills, critical thinking, and learning outcomes through the implementation of the CANGKAL model using Wordwall media. This Classroom Action Research (CAR) was conducted over four meetings in the second semester of the 2024/2025 academic year, involving 14 students. The study used a qualitative approach, with data collected through observations of teacher and student activities, and written tests to assess learning outcomes, collaboration, and critical thinking skills. The findings showed improvements in all observed aspects. Teacher activity reached the "very good" category, while student activity increased from "moderately active" to "very active". Collaboration and critical thinking skills also improved significantly, from "moderately skilled" to "highly skilled". These improvements positively impacted student learning outcomes, which increased classically from one meeting to the next. It can be concluded that the CANGKAL model combined with Wordwall media effectively enhances the quality of learning. It is recommended as an alternative model to improve student engagement and overall academic performance).